Sérgio Abreu e seu tempo - Amorim, Humberto; Dias, Ricardo; de Almeida Ribeiro, Felipe; Poletto, Fabio (Revista Vórtex, 2023)
"Sérgio Abreu y su tiempo", volumen 1 de la serie de libros electrónicos de la Revista Vórtex. Humberto Amorim, Ricardo Dias, Felipe de Almeida Ribeiro, Fabio Guilherme Poletto (organizadores)